Diversitas Produk Anti Polutan Dan Marketing E-Bisnis Pada Desa Maesan, Kec. Mojo Kediri - Sri Herianingrum; Sylva Alif Rusmita; Lina Nugraha Rani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Maesan Village is located in Mojo District, Kediri Regency, East Java Province. In this village, there are farmer groups who have major problems, including in this case pollution due to the use of tin waste, secondly it is still dependent on middlemen who provide low interest prices so they need a way to release dependence on middlemen, third is about financial records. With the case study method of the Kembang Karomah farmer group, in this community service, the solution that will be discussed in this paper is product diversity to increase selling prices, then e-marketing to cut middlemen, when providing insights for recording financial reports. The results of this research and community service are that the Kemabang Karomah farmer group is able to increase their knowledge of human resources and is ready to diversify products to anti-pollutant plants, and be able to use e-marketing applications.